2019
DOI: 10.3390/medicina55080411
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Angle-Specific Isokinetic Hamstring to Quadriceps Ratio Using Multilevel Generalized Additive Models

Abstract: Background and Objectives: This study considered the use of a generalized additive multilevel model to describe the joint-angle-specific functional hamstring to quadriceps ratio (H:Q ratio) in the knee, using all of the available truly isokinetic data within the range. Materials and Methods: Thirty healthy male basketball players aged 15.0 (1.4) years (average stature = 180.0 cm, SD = 11.1 cm; average body mass = 71.2, SD = 14.9 kg) years were considered. All players considered had no history of lower extremit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Based on the reviewed evidence (Table 5 ), most studies have reported that the angle of peak torque during eccentric tests is in the range 30–40° flexion, which is similar to that observed during concentric contractions. Further, most studies that examined either the shape of torque-joint angle relation or angle of peak torque have reported no differences between the two contraction types [ 153 , 215 , 216 , 225 , 230 ] . Only two studies provided evidence that peak concentric isokinetic torque occurs at a greater knee flexion angle (shorter length) than peak eccentric torque [ 24 , 153 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the reviewed evidence (Table 5 ), most studies have reported that the angle of peak torque during eccentric tests is in the range 30–40° flexion, which is similar to that observed during concentric contractions. Further, most studies that examined either the shape of torque-joint angle relation or angle of peak torque have reported no differences between the two contraction types [ 153 , 215 , 216 , 225 , 230 ] . Only two studies provided evidence that peak concentric isokinetic torque occurs at a greater knee flexion angle (shorter length) than peak eccentric torque [ 24 , 153 ].…”
Section: Main Textmentioning
confidence: 99%
“…4) and hip moment arm (Table 1) as the hip flexes. Irrespective of hip flexion angle, the maximum knee flexion torque is centered around 30° of knee flexion (Table 5) and ranges between 0 and 45° of knee flexion during isometric [79, 127, 130, 145, 149, 150, 152-155, 158, 198-202] and 15-70° during isokinetic [20,24,128,153,158,192,[203][204][205][206][207][208][209][210][211][212][213][214][215][216][217][218][219][220][221] tests. Several studies have also shown that the maximum knee flexion torque occurred at more flexed knee angles when the hip was more flexed [127,144,145,206] which makes sense given that this would approximately maintain muscle length; i.e., the muscle length rather than the joint angles themselves appear to dictate muscle strength.…”
Section: Torque-angle Relationshipmentioning
confidence: 99%
“…As the pain level has been proven to be associated with peak torque reduction especially during extension movements [ 49 ], and the specific angle of pain occurrence may help to further analyze the biomechanical mechanisms behind the abnormal IMC. For future research, extracting IMC features of specific knee injuries from a large number of IMC using deep learning related algorithms [ 50 ], while incorporating essential angle-specific and/or speed-specific quantitative data from isokinetic testing in the building of the predictive model might be a promising approach [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%